LTBK-04. PHASE 2 MULTICENTER STUDY OF THE ONCOLYTIC ADENOVIRUS DNX-2401 (TASADENOTUREV) IN COMBINATION WITH PEMBROLIZUMAB FOR RECURRENT GLIOBLASTOMA; CAPTIVE STUDY (KEYNOTE-192). (20th November 2020) - Zadeh, Gelareh; Daras, Mariza; Cloughesy, Timothy F; Colman, Howard; Kumthekar, Priya U; Chen, Clark C; Aiken, Robert; Groves, Morris D; Ong, Shirley; Ramakrishna, Rohan; Vogelbaum, Michael A; Khagi, Simon; et al.
Abstract: BACKGROUND: A Phase 2 multi-center study was conducted to evaluate the replication-competent oncolytic adenovirus, DNX-2401 (tasadenoturev), in combination with the anti-PD-1 antibody, pembrolizumab, in subjects with recurrent glioblastoma. METHODS: Subjects ≥ 18 years with glioblastoma at first or second recurrence were treated with a single intratumoral injection of 5e8-5e10 vp DNX-2401 at the time of biopsy, followed by 200 mg pembrolizumab infusions every 3 weeks until progression or toxicity. RESULTS: Forty-nine subjects were enrolled at first (79.6%) or second (20.4%) recurrence after prior surgery (89.8%), radiotherapy (100%), and temozolomide (100%). Forty-eight of 49 (98%) were treated with 5e8 vp (n=3), 5e9 vp (n=3), or 5e10 vp (n=42) DNX-2401 and pembrolizumab. Median treatment duration was 7 cycles (range 1–35) with one subject remaining on treatment (cycle 31). Adverse events were primarily mild to moderate, consistent with underlying disease, and manageable. Headache, brain edema, and fatigue are the most common events reported as related to the treatment regimen. Of subjects treated with full dose DNX-2401 and pembrolizumab (n=42), 5 subjects (11.9%) had confirmed responses, including 2 durable ongoing complete responses and 3 partial responses. One subject remains tumor free > 12 months after completing the planned 24 months of pembrolizumab. Median overall survival was 12.5 months; OS-12 and OS-18 were 54.5% and 20.8%, respectively. Four subjects, all of which have survived more than 21 months, continue to be followed for survival. CONCLUSIONS: DNX-2401 plus pembrolizumab provides encouraging activity and is safe in patients with recurrent glioblastoma. A global, randomized, controlled Phase 3 study is planned.